2016
DOI: 10.1128/aac.00658-16
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin MIC Does Not Predict 90-Day Mortality, Readmission, or Recurrence in a Prospective Cohort of Adults with Staphylococcus aureus Bacteremia

Abstract: Staphylococcus aureus is a leading cause of bacteremia (1, 2). Even when an individual is appropriately treated, the risk of mortality from S. aureus bacteremia (SAB) is 20 to 40% per episode (3-8). Furthermore, the morbidity from SAB is striking, with 10 to 15% of episodes being complicated by endocarditis or a risk of metastatic disease elsewhere in the body (9, 10). The financial consequences of SAB are also significant, with health care costs ranging from $12,078 to $25,573 per episode of SAB (11-13). Typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 77 publications
2
10
0
Order By: Relevance
“…In addition, a recent cohort study of Danish patients with community‐acquired S. aureus bloodstream infection found patients with chronic heart failure had a higher rate of 90‐day mortality compared to those without chronic heart failure; however, the proportion of patients with MRSA in this study was extremely low, making direct comparisons difficult . Notably, vancomycin MIC had no impact on clinical outcome, which is consistent with two recently published studies …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, a recent cohort study of Danish patients with community‐acquired S. aureus bloodstream infection found patients with chronic heart failure had a higher rate of 90‐day mortality compared to those without chronic heart failure; however, the proportion of patients with MRSA in this study was extremely low, making direct comparisons difficult . Notably, vancomycin MIC had no impact on clinical outcome, which is consistent with two recently published studies …”
Section: Discussionsupporting
confidence: 89%
“…28 Notably, vancomycin MIC had no impact on clinical outcome, which is consistent with two recently published studies. 29,30 It is possible that b-lactam therapy, particularly piperacillin-tazobactam, in combination with vancomycin leads to higher frequency of nephrotoxicity compared to vancomycin alone. [31][32][33] The majority of patients in COMBO received piperacillin-tazobactam.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding mortality effect, some prior studies on the relationship between vancomycin MIC and outcomes in MSSA BSI have found an increased mortality risk (19,20) associated with MICs Ն 2 mg/liter, however other recent studies have failed to demonstrate a statistically significant difference in death rates (2,23,26). A metaanalysis looking at effect of vancomycin MIC on mortality in S. aureus bacteremia failed to show a significant difference in 30-day mortality rates in SAB across a range of vancomycin MIC cutoffs (21).…”
Section: Discussionmentioning
confidence: 99%
“…The RVS phenotype in MSSA infection has recently been studied for its effect on clinical outcome. In particular, it has been linked to increased risk of mortality in some studies, although other analyses have failed to show robust associations with clinical outcome (15,(17)(18)(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…Whether this was the cause or an effect of treatment failure is uncertain, particularly given that the patient with ventilator-associated pneumonia caused by a virtually identical isolate with a vancomycin MIC of 2 g/ml responded to vancomycin. The importance of vancomycin MICs of Ͼ1 mg/ml as a predictor of treatment failure (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) has been hotly debated. In neither of these cases was the MIC a particularly good predictor.…”
Section: Commentarymentioning
confidence: 99%